FACTORS AFFECTING SERUM PARAOXONASE 1 ACTIVITY IN MIGRANT AND RESIDENT GUJARATI SOUTH ASIANS. Issue 1 (2014) - Patel, Jeetesh; Mirrielees, Rebecca; Vyas, Avni; Cruickshank, Kennedy; Prabhakaran, Dorairaj; Bhatnagar, Deepak; Mackness, Bharti; Reddy, K. Srinath; Hughes, Elizabeth; Durrington, Paul; Mackness, Michael
No abstract available